The phoenix motif during the decline of the Sassanid Empire (600-700AD) / Maryam Borzouyan Dastjerdi - Maryam Borzouyan , Dastjerdi (2017)
The current research investigates the Sassanid phoenix that had been created during ancient time in Persia (Iran). Sassanid dynasty is the last Persian Empire before the emergence of Islam in the country. This research examines the Sassanid phoenix which is an imaginative hybrid creature that looks like a winged mammal. Historians and Iranian studies scholars suggest that the body parts of this creature comprise of the dog, lion, eagle and peacock. These animals are part of the Sassanid phoenix and were considered sacred and some had cultural value during the ancient times. So, the current research examines the iconic value of each part of this creature according to Erwin Panofsky’s theory about iconography and iconology in three steps, which include, formal art analysis, studying the subject matter, investigating cultural and religious values related to the subject matter. Then, the researcher selected five samples of Sassanid phoenix motifs. Firstly a formal analysis of each composite part of the phoenix (head, wings, claws, and tail) is carried out. Then the significance of each composite part is examined within the historical context of the Sassanid Empire and its neighboring countries, by referencing historical books, sacred texts and literature.